Risk management in the system of financial stabilityof the service enterprise - Svetlana Drobyazko; Anna Barwinska-Malajowicz; Boguslaw Slusarczyk; Olga Chubukova; Taliat Bielialov (Journal of Risk and Financial Management, 2020)
The article is devoted to the theoretical substantiation and development of methodological approaches and practical recommendations for modeling the assessment of the financial stability of a service sector enterprise. To assess the financial condition of the hotel industry, a visual interpretation of the neural network, a model of self-organizing Kohonen map, was used. It is proven that by the method of Kohonen maps for each service provided by the hotel industry, in a certain period of activity, it is possible to establish certain objective limitations of structural characteristics that will prevent the transition to problem clusters or ensure the transition to better ones. The authors propose an economic and mathematical model of the process of assessing financial stability by calculating the integral indicator of financial stability of the service sector. The types of control maps for each of the coefficients that have a significant impact on the assessment of the financial stability of the enterprise in the service sector were identified. Control maps were constructed for each coefficient, which are part of the integrated indicator of financial stability, and their analysis was carried out for the presence of special reasons for the variability of the process of financial stability assessment. The concept of modeling a system for assessing the financial stability of service enterprises is developed in the article, which is based on the collection of financial data, a comprehensive analysis of factors influencing the financial condition, a study of the controllability of the process of assessing financial stability, building a model of an integral indicator of financial stability, and its program implementation.
Keywords: 330; risk management; financial stability; coefficient of seasonality; control chart; expert system